Improving the Methodology for Using Digital Technologies in the Formation of Professional Competence of Future Physics Teachers - Qurbonov, Maqsudali (International Journal on Human-Computing Studies, 2023)
the article presents methodological ways to determine the qualitative characteristics of training in the framework of physics, taking into account the formation of professional competence of the future physics teacher as a qualitatively new type of Education.